Penguatan Literasi Pertanian untuk Meningkatkan Minat Generasi Muda terhadap Dunia Tani - Nursamsi, Nursamsi; Sari, Dyah Puspita; Syofiani, Riza; Hudia, Hudia; Suhadi, Suhadi; Amir, Syafri; Zudri, Fatardho; Yuska, Dian Aulia Tri; Nasution, Mona Turisna; Novfirman, Novfirman; Maulana, Ingga Pragesti (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2026)
The declining interest and participation of young generations in the agricultural sector pose a serious challenge to the sustainability of agricultural development, including in Kamang Tangah Anam Suku Village, Agam Regency, West Sumatra. Despite its commitment to developing as an organic food production center, the village faces limited involvement of millennial and Generation Z farmers, which threatens the continuity of environmentally sustainable agriculture. This community service program aimed to strengthen agricultural literacy and increase young people’s interest in farming through an educational and participatory approach. The program was implemented through a preliminary survey, problem identification, organic agriculture literacy counseling for youth aged 15–30 years, and evaluation using pre-test and post-test methods. The counseling activities were delivered interactively by engaging young agricultural practitioners and incorporating contextual discussions based on local experiences. The results showed a significant improvement in participants’ knowledge, positive perceptions, and interest in agriculture, with an average increase in agricultural literacy of approximately 45%. Furthermore, the program successfully facilitated the establishment of the Agro Muda Kreatif Millennial Farmer Group, consisting of 19 millennial and Generation Z youths, as a tangible outcome of the intervention. These findings indicate that strengthening agricultural literacy through approaches aligned with youth characteristics is effective in encouraging farmer regeneration